2017
DOI: 10.4172/2155-6148.1000794
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Communication Tools on the Efficiency of Anesthesiologists in the Perioperative Setting

Abstract: ObjectiveTo assess if Real Time Locating Systems (RTLS) technology has an effect on the perioperative efficiency of anesthesiologists at our institution.MethodsA retrospective chart review was performed for all outpatient and short-stay patients who received general anesthesia and monitored anesthesia care between January and June of 2016. Patients over 18 years with an ASA classification of 1, 2, and 3 were included. Time was used as a measure of efficiency between two groups of anesthesiologists.These two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…In our initial study, we investigated two time points during the anesthesiologist's workflow to determine if any difference exists in efficiency between those who have access to RTLS (JRSC) and those who do not (Main Campus). We found that anesthesiologists who utilize RTLS were consistently faster, and hence more efficient in their perioperative workflow [12]. While our results were statistically significant, there were confounding factors which could have accounted for the difference in perioperative efficiency.…”
Section: Introductionmentioning
confidence: 44%
See 2 more Smart Citations
“…In our initial study, we investigated two time points during the anesthesiologist's workflow to determine if any difference exists in efficiency between those who have access to RTLS (JRSC) and those who do not (Main Campus). We found that anesthesiologists who utilize RTLS were consistently faster, and hence more efficient in their perioperative workflow [12]. While our results were statistically significant, there were confounding factors which could have accounted for the difference in perioperative efficiency.…”
Section: Introductionmentioning
confidence: 44%
“…There are several time points in the perioperative period that involve anesthesiologists, where improved efficiency may translate to a decrease in operating room time and reduced healthcare costs. Our previous study concluded that anesthesiologists at our institution with access to RTLS were significantly more efficient in completing their preoperative anesthesia evaluation (p < 0.0001) than those without access to RTLS [12]. This follow-up study attempts to eliminate variability and focuses on the time difference between when a patient enters the OR to the time of induction for only the first cases of the day between anesthesiologists without (Group 1) and with RTLS (Group 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our prior studies, we demonstrated that anesthesiologists at our institution with access to RTLS were significantly more efficient in their perioperative workflow ( p <0.0001) than those without access to RTLS[12,13]. While recognizing several confounding factors, we concluded that access to RTLS improves perioperative efficiency of anesthesiologists in two ways: It provides OR staff the ability to track the location of an entire OR team, including the patient, in real-time, which may allow for a more efficient process in deeming an OR “ready”.The awareness that one is being tracked and monitored may motivate all OR staff, including anesthesiologists, to be readily available once the OR is deemed “ready”[14].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare settings have experimented with using RTLS in various capacities, from tracking clinician locations to finding patients as they proceed through different locations for their care. [7][8][9] However, best practices for the most effective and efficient use of RTLS capabilities for clinical workflow have yet to be defined. 10 Nevertheless, this technology can help pinpoint key areas where clinical improvements can be most effective.…”
Section: Introductionmentioning
confidence: 99%